Influence of the implantation of a dynamic inter-spinous stabilizer for a functioning condition and pain ailments of patients with the discopathy of lumbar spine - Spandel, Sylwia; Bąk, Ewelina; Spandel, Leszek; Krzemińska, Sylwia (Journal of Education, Health and Sport, 2017)
Introduction <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: normal; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;"> <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: normal; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">The lumbar disc herniation is a common health problem of modern society. In many cases it requires operational intervention. <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: normal; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;"> <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: normal; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">Objective <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: normal; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">The aim of this paper is to evaluate the effect of DIAM TM interactions on intraoperative stabilizers in functional and pain levels in patients with lumbar spine dysopatia. <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: normal; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;"> <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: normal; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">Material and methods <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: normal; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;"> <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: normal; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">The study included 52 patients who underwent spinal disc herniation. Oswestry (ODI), Visual Analog Scale (VAS), and the author's questionnaire were used to test the effect of the procedure. <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: normal; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;"> <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: normal; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">Results <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: normal; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;"> <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: normal; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">In the study group, the mean ODI score before surgery was 20.81 (± 5.99), and after 6 months after surgery the rate was significantly lower than 12.94 (± 5.42). Average intensity of pain acc. For VAS before and after surgery respectively 3.15 (± 1.28) and 1.58 (± 1.14). <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: normal; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;"> <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: normal; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">Conclusions <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: normal; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;"> <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: normal; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">Implementing an internal DIAM TM in a short period of time leads to a significant reduction in pain and improved patient functioning.